2020
DOI: 10.21203/rs.3.rs-24817/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Drivers of Tobacco use Among Young Men in Sub-Saharan Africa: Evidence from 21 Nationally Representative Surveys

Abstract: Background Tobacco consumption – including smoking, chewing tobacco and snuff has been recognized as a global public health issue and a major cause of premature mortality and morbidity. An annual estimated figure of more than 7 million people dies due to tobacco consumption with more than 6 million of those deaths attributed to direct tobacco use and about 890, 000 resulting from exposure to second-hand smoke. This paper seeks to examine the prevalence and drivers of tobacco use among young men in sub-Saharan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…These findings are in line with the available evidence in Africa, where observational studies have identified that, being male, older age, lower education status and lower SES are associated with tobacco use and harmful use of alcohol in Africa [75,76]. Similarly increasing age; being female; residing in urban areas; formal employment; higher education; and higher SES have been reported in several studies to be associated with being overweight, obesity and physical inactivity in African settings [65,66,77,78].…”
Section: Summary and Discussionsupporting
confidence: 89%
“…These findings are in line with the available evidence in Africa, where observational studies have identified that, being male, older age, lower education status and lower SES are associated with tobacco use and harmful use of alcohol in Africa [75,76]. Similarly increasing age; being female; residing in urban areas; formal employment; higher education; and higher SES have been reported in several studies to be associated with being overweight, obesity and physical inactivity in African settings [65,66,77,78].…”
Section: Summary and Discussionsupporting
confidence: 89%